2022
DOI: 10.3390/ijerph19052512
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Infection Transmission Routes through Exhaled Breath and Cough Particle Dispersion in a General Hospital

Abstract: Identifying infection transmission routes in hospitals may prevent the spread of respiratory viruses and mass infections. Most previous related research focused on the air movement of passive tracers, which typically represent breathing. In this study, particle evaporation and dispersions with various particle sizes were applied to evaluate particle movement because of breathing and coughing using computational fluid dynamics (CFD) simulations. Pyeongtaek St. Mary Hospital, where a Middle East respiratory synd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…When the purifier was run alone in this study, it showed poor effects on some locations, which was greatly related to the purifier ventilatory efficiency and room layout. For example, in a ward with a patient with SARS-CoV-2, the virus was widely distributed on the floor, a computer mouse, trash buckets, and the patient’s bedside banister and was detected in the air about 4m away from the patient [ 37 ], even as the air flow reached the outside of the ward [ 38 ]. Interestingly, PNOI produces ions capable of diffusing everywhere with the aid of the ventilation system and the airflow of HEPA.…”
Section: Discussionmentioning
confidence: 99%
“…When the purifier was run alone in this study, it showed poor effects on some locations, which was greatly related to the purifier ventilatory efficiency and room layout. For example, in a ward with a patient with SARS-CoV-2, the virus was widely distributed on the floor, a computer mouse, trash buckets, and the patient’s bedside banister and was detected in the air about 4m away from the patient [ 37 ], even as the air flow reached the outside of the ward [ 38 ]. Interestingly, PNOI produces ions capable of diffusing everywhere with the aid of the ventilation system and the airflow of HEPA.…”
Section: Discussionmentioning
confidence: 99%
“…With the help of Gustin et al (2011)'s experiments in which tests of exhaled air from ferrets were analyzed, there was a significant difference in the particle size distribution between normal breathing and sneezing, as shown in Fig. 4, with coughing and breathing producing particle sizes in the 0.5-15-μm range, whether inoculated by intranasal or by aerosol infection with H 3 N 2 influenza virus (A/Panama/2007/1999; PN99) ferrets, the number of aerosol particles released decreases with increasing particle size, and the number of aerosols is already close to 0 when the particle size is greater than 5 m. And it is clear from the figure that the total number of particles released during coughing is much greater than that during breathing, and that more than three times as many aerosols less than 1 m are released during coughing as during breathing; for the same particle size, the difference between the number of particles released from coughing and breathing can be up to four times larger, while the size of particles released by a person during coughing is also tens to hundreds of times larger than during breathing (Jung et al 2022). It has been reported that patients with COVID-19 suffer from symptoms such as dry and short coughs and that different cough mechanisms may produce carrier droplets of different sizes (Ghinai et al 2020).…”
Section: Viral Load Of Infected Personsmentioning
confidence: 92%
“…Although droplet sizes expelled by all types of respiratory activity range widely, droplets larger than 100 µm usually cannot travel long distances or will evaporate rapidly during transport (Jung et al 2022), so most droplet sizes in aerosol propagation experiments are much smaller than in close contact experiments. At the same time, longer-range transport requires consideration of the effects of airflow organization on aerosol particles and inevitably suffers from uncertainty in the respiratory deposition of airborne pathogens due to air turbulence, which directly affects the intake of airborne pathogens (Sze To and Chao 2010).…”
Section: Inter-individual Distancesmentioning
confidence: 99%
“…Droplets sized under 50 μm stayed airborne for a significant enough time to be inhaled and transported through the air over long distances with the wind. 22 23 Droplets larger than 100 μm tend to fall near the emission source due to gravitational sedimentation. 23 24 Therefore, the droplets in the range of 1–100 μm with the number of 4,800 were considered to investigate the airborne transmission.…”
mentioning
confidence: 99%
“… 22 23 Droplets larger than 100 μm tend to fall near the emission source due to gravitational sedimentation. 23 24 Therefore, the droplets in the range of 1–100 μm with the number of 4,800 were considered to investigate the airborne transmission. 24 25 26 All particles contacted with the surface were considered to be deposited.…”
mentioning
confidence: 99%